2019
DOI: 10.1038/s41467-019-10931-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of egg coat cross-linking sheds light on ZP1-associated female infertility

Abstract: Mammalian fertilisation begins when sperm interacts with the egg zona pellucida (ZP), whose ZP1 subunit is important for fertility by covalently cross-linking ZP filaments into a three-dimensional matrix. Like ZP4, a structurally-related component absent in the mouse, ZP1 is predicted to contain an N-terminal ZP-N domain of unknown function. Here we report a characterisation of ZP1 proteins carrying mutations from infertile patients, which suggests that, in human, filament cross-linking by ZP1 is crucial to fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 84 publications
3
69
2
Order By: Relevance
“…In relation to these considerations, it will be essential to gain much more detailed information on the structure of the egg coat than what is currently known. Obtaining this knowledge will not only depend on further X-ray crystallographic studies of isolated ZP subunits or domains thereof, an approach that already yielded precious information on ZP1 (Nishimura et al, 2019), ZP2 (Bokhove et al, 2016), and ZP3 (Han et al, 2010;Monné et al, 2008), as well as a first example of how sperm recognizes the egg coat in an invertebrate model of FAHRENKAMP ET AL.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In relation to these considerations, it will be essential to gain much more detailed information on the structure of the egg coat than what is currently known. Obtaining this knowledge will not only depend on further X-ray crystallographic studies of isolated ZP subunits or domains thereof, an approach that already yielded precious information on ZP1 (Nishimura et al, 2019), ZP2 (Bokhove et al, 2016), and ZP3 (Han et al, 2010;Monné et al, 2008), as well as a first example of how sperm recognizes the egg coat in an invertebrate model of FAHRENKAMP ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with these findings on mouse fertilization, residues such as mannose, fucose, GlcNAc, and the sialyl-Lewis X sequence [NeuAcα2-3Galβ1-4(Fucα1-3)GlcNAc] of N-and O-glycans have been suggested to play a role in human egg-sperm binding (Miranda et al, 1997;Oehninger, Patankar, Seppala, & Clark, 2009;Pang et al, 2011). The importance of these chemical moieties may explain the different sperm-binding properties of affinity-purified native human ZP proteins (Chiu et al, 2008) and a recent crystallographic analysis of chicken ZP1-N1 homodimers (Nishimura et al, 2019) suggested that core fucosylation of a conserved N-glycan that immediately precedes the intermolecular disulfide of the protein may favor a specific conformation of the ZP filament cross-links.…”
Section: Zp3 Deglycosylationmentioning
confidence: 99%
See 3 more Smart Citations